Sistem Pemberian Pakan Hamster Otomatis berbasis Mikrokontroler - Nurul Aulia, Farah; Aisuwarya, Ratna (CHIPSET, 2024)
This research aims to create an automatic hamster feeder system at night following the nocturnal nature of hamsters. The system will be given a command in the form of a message via the Telegram messaging application to fill the hamster's weight which will be calculated as a calculation of the hamster's daily feed portion. The nature of hamsters which are generally nocturnal, in contrast to humans who usually rest at night, makes it difficult for humans to feed their hamsters at night regularly. The daily portion of hamster food is around 0.11 times the hamster's body weight and this provision must be appropriate not to cause obesity in the hamster. Based on these circumstances, this research is proposed as a solution to this problem. After filling the hamster's weight information, the system will calculate the hamster's daily food weight and when the sensor catches that the hamster approaching the system, the system will immediately open the servo motor to pour the hamster food.